2022
DOI: 10.3390/ijerph19020946
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Back Pain in Children and Adolescents from the Region of Murcia (Spain): ISQUIOS Programme

Abstract: Puberty is a vulnerable period for musculoskeletal disorders due to the existence of a wide inter-individual variation in growth and development. The main objective of the present study was to describe the prevalence of back pain (BP) in the past year and month in school-aged children according to sex, age, maturity status, body mass index (BMI) and pain characteristics. This study involved 513 students aged between 9 and 16 years. Anthropometric measures were recorded to calculate the maturity stage of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…The results showed, as in other research studies, that the area of the body with a high prevalence was the lumbar region [6,18], with a low prevalence found in the cervical region [5,18]. Previous research shows a different prevalence of SP results among adolescents, ranging from 10.7% to 78.5% [4,5,18]. These differences in the prevalence of pain are the result of the different periods of time studied (from one week to lifetime), the areas included [4], and/or characteristics of the sample utilized for each research study.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The results showed, as in other research studies, that the area of the body with a high prevalence was the lumbar region [6,18], with a low prevalence found in the cervical region [5,18]. Previous research shows a different prevalence of SP results among adolescents, ranging from 10.7% to 78.5% [4,5,18]. These differences in the prevalence of pain are the result of the different periods of time studied (from one week to lifetime), the areas included [4], and/or characteristics of the sample utilized for each research study.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, a high prevalence of SP was observed in adolescents in the past year. The results showed, as in other research studies, that the area of the body with a high prevalence was the lumbar region [6,18], with a low prevalence found in the cervical region [5,18]. Previous research shows a different prevalence of SP results among adolescents, ranging from 10.7% to 78.5% [4,5,18].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations